Community transmission of monkeypox in the United Kingdom, April to May 2022 - Vivancos, Roberto; Anderson, Charlotte; Blomquist, Paula; Balasegaram, Sooria; Bell, Anita; Bishop, Louise; Brown, Colin S; Chow, Yimmy; Edeghere, Obaghe; Florence, Isaac; Logan, Sarah; Manley, Petra; et al. (Euro surveillance : bulletin européen sur les maladies transmissibles, 2022)
Between 7 and 25 May, 86 monkeypox cases were confirmed in the United Kingdom (UK). Only one case is known to have travelled to a monkeypox virus (MPXV) endemic country. Seventy-nine cases with information were male and 66 reported being gay, bisexual, or other men who have sex with men. This is the first reported sustained MPXV transmission in the UK, with human-to-human transmission through close contacts, including in sexual networks. Improving case ascertainment and onward-transmission preventive measures are ongoing.